Results from Bottom Trawl Survey on Flemish Cap of June-July 2016. - Casas-Sánchez, José Miguel; González-Troncoso, Diana (2017)
A stratified random bottom trawl survey on Flemish Cap was carried out from June 22th to July 23th 2016. The area surveyed was extended up to depths of 800 fathoms (1460 meters) following the same procedures as in previous years and 181 fishing stations planned. The survey was carried out by the R/V Vizconde de Eza with the usual survey gear (Lofoten). A total of 181 valid hauls were made by the vessel R/V Vizconde de Eza, 120 up to 730 meters depth and 61 up to 1460 meters. Survey results including abundance indices of the main commercial species and age distributions for cod, redfish, American plaice, Greenland halibut, roughhead grenadier and shrimp are presented. The general indexes for this year are estimated taken into account the traditional swept area (strata 1- 19, up to depths of 730 m.) and the total area surveyed (strata 1-34, up to depths of 1460 m.). SI